Risk, the required rate of return, and aspects of South African management practice - S. Paulo; J. K. Bosch (South African Journal of Business Management, 1992)
The pivotal role of the required rate of return to all financial decisions is well documented in the financial literature. However, many misconceptions exist with regard to the specification of the components of the required rate of return. In order to learn more about the possible components of the required rate of return, particularly the different risk premia, empirical information on the determination and use of the required rate of return by South African financial managers was obtained. From the findings of the empirical survey it was evident that the required rate of return is adjusted for a variety of risks. This enables the inference to be drawn that risk adjusted discount rates are being used when taking financial decisions. Further, it is evident that sensitivity analysis and judgemental approaches are used when adjustments are made to the required rate of return.
Keywords: 650